Pengaruh Penerapan Model Flipped Classroom Menggunakan Video Interaktif Melalui Edpuzzle Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Menengah Atas Negeri 1 Praya Barat - Widia, Yenna; Nasrullah, Ahmad (Mathematic Education Departement, State Islamic University of Mataram, 2025)
This article aims to test the effect of implementing the flipped classroom model using interactive videos through edpuzzle on students' critical thinking skills at State Senior High School 1 Praya Barat. The sample in this study consisted of class X7 as the control class and X8 as the experimental class. The research approach used a Quasi experiment type of Non-equivalent Control Group Design. The data analysis technique was through nonparametric statistical tests. Because the initial abilities between the control and experimental classes were not equal, to answer the problem formulation, an N-Gain Score test was conducted to find the average difference between the control and experimental classes. As a result, it was found that the experimental class had an average N-Gain of 0.35 which was included in the medium category, and the control class achieved an average of 0.22 which was in the low category. The increase in the experimental class was higher than in the control class, so it can be concluded that the flipped classroom model using interactive videos through Edpuzzle has an effect on students' critical thinking skills.